Copolymers of starch, a sustainable template for biomedical applications: A review. (15th February 2022) - Sarder, Roman; Piner, Emily; Rios, David Cruz; Chacon, Lisandra; Artner, Mirela Angelita; Barrios, Nelson; Argyropoulos, Dimitris
Abstract: The outstanding versatility of starch offers a source of inspiration for the development of high-performance-value-added biomaterials for the biomedical field, including drug delivery, tissue engineering and diagnostic imaging. This is because starch-based materials can be tailored to specific applications via facile grafting or other chemistries, introducing specific substituents, with starch being effectively the "template" used in all the chemical transformations discussed in this review. A considerable effort has been carried out to obtain specific tailored starch-based grafted polymers, taking advantage of its biocompatibility and biodegradability with appealing sustainability considerations. The aim of this review is to critically explore the latest research that use grafting chemistries on starch for the synthesis of products for biomedical applications. An effort is made in reviewing the literature that proposes synthetic "greener" approaches, the use of enzymes and their immobilized analogues and alternative solvent systems, including water emulsions, ionic liquids and supercritical CO2 . Graphical abstract: Unlabelled Image